2018
DOI: 10.1038/s41419-018-0316-4
|View full text |Cite
|
Sign up to set email alerts
|

Impaired autophagic flux is associated with the severity of trauma and the role of A2AR in brain cells after traumatic brain injury

Abstract: Recent studies have shown that after traumatic brain injury (TBI), the number of autophagosomes is markedly increased in brain cells surrounding the wound; however, whether autophagy is enhanced or suppressed by TBI remains controversial. In our study, we used a controlled cortical impact system to establish models of mild, moderate and severe TBI. In the mild TBI model, the levels of autophagy-related protein 6 (Beclin1) and autophagy-related protein 12 (ATG12)-autophagy-related protein 5 (ATG5) conjugates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…Therefore, yellow dots (merged red and green dots) represent autophagosomes, while red dots represent autophagolysosomes. If autophagy is activated and autophagic flux is normal, red dots will dominate over yellow dots; if autophagic flux is impaired, more yellow dots than red dots will be observed 50 , 51 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, yellow dots (merged red and green dots) represent autophagosomes, while red dots represent autophagolysosomes. If autophagy is activated and autophagic flux is normal, red dots will dominate over yellow dots; if autophagic flux is impaired, more yellow dots than red dots will be observed 50 , 51 .…”
Section: Methodsmentioning
confidence: 99%
“…How NIX-related mitophagy exerts its effect at later times following TBI also needs to be understood, as does NIX-mediated apoptosis. It is reported that autophagy functions differently with various degrees of damage 51 . Therefore, the effects of autophagy or mitophagy in other forms of TBI-induced damage are likewise ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Through this pathway, the contents are degraded following fusion with the lysosomal compartment [28]. However, abnormalities in any of the above stages may lead to autophagic flux disorders and further disturb the physiological activity of the body [135,136].…”
Section: The Involvement Of Autophagy Dysfunction In Organelle Impairmentioning
confidence: 99%
“…Normal autophagy can remove abnormally synthesized proteins in cells and digest damaged and redundant organelles, which is beneficial for intracellular homeostasis. However, abnormalities in any of the above stages may lead to autophagic flux disorders and further disturb the physiological activity of the body [ 135 , 136 ].…”
Section: Introductionmentioning
confidence: 99%